Ar de Rock O Boom do Rock em Portugal no Início da Década de 1980 - Andrade, Ricardo (Contemporânea, 2023)
Songs like Chico Fininho, by Rui Veloso and the Banda Sonora, and Cavalos de Corrida, by the group UHF, were the first hits of the "Portuguese rock boom", an expression referring to the first moment of great commercial success for rock repertoire recorded and published in Portugal. At the beginning of the 1980s, "Portuguese rock" was central to the consolidation of a "modern" and cosmopolitan youth identity that increasingly identified with habits and lifestyles from the Anglo-American cultural universe. The intensification of the editorial commitment to this repertoire led to the emergence of new groups, record producers, sound companies and artist agencies, as well as the reconfiguration of the characteristics of various bands that sought to align themselves with the phenomenon, including the growing use of the Portuguese language, an aspect that until then had often been disregarded in the context of rock music. This book analyses the main changes that took place in rock practices in Portugal during the second half of the 1970s and early 1980s, looking at the links between the various music industries and the role of their agents as active participants in shaping the activity of the groups and their respective repertoires.